The writing of Jesús Urzagasti: poetic of the wide open - Daona, María José (Revista Chilena de Literatura, 2019)
In this work, I analyze the poetry of the Bolivian writer Jesús Urzagasti as an “poetic of the wide open”. His writing suppresses the sense of deprivation and abandonment of open-air life and builds a province, with a tree at its center, as a propitious place to “inhabit”. Trees and horses representations show a territory left behind, which lives inside the subject. He succumbs constantly, to the memory of a happy past sheltered between the sky and the earth. The poetic word allows the return of the province that returns transformed into an oneiric dwelling during night and dream.